Determination of chlorinated paraffins and olefins in plastic consumer products of the Swiss market - O. Mendo Diaz; A. Tell; S. Hangartner; J. Hutter; U. Stalder; H. Friedl; A.M. Buser; S. Kern; L. Bigler; D. Bleiner; N.V. Heeb (Chemosphere, 2025)

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

High content analysis of in vitro alveolar macrophage responses can provide mechanistic insight for inhaled product safety assessment - V. Hutter; S. Hopper; J. Skamarauskas; E. Hoffman (Toxicology in Vitro, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Combining Extracellular miRNA Determination with Microfluidic 3D Cell Cultures for the Assessment of Nephrotoxicity: a Proof of Concept Study - Laura Suter-Dick; L. Mauch; D. Ramp; M. Caj; M. K. Vormann; S. Hutter; H. L. Lanz; J. Vriend; R. Masereeuw; M. J. Wilmer (The AAPS Journal, 2018)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

A population genomic approach to map recent positive selection in model species - P. PAVLIDIS; S. HUTTER; W. STEPHAN (Molecular Ecology, 2008)
Based on nearly complete genome sequences from a variety of organisms data on naturally occurring genetic variation on the scale of hundreds of loci to entire genomes have been collected in recent years. In parallel, new statistical tests have been developed to infer evidence of recent positive selection from these data and to localize the target regions of selection in the genome. These methods have now been successfully applied to Drosophila melanogaster , humans, mice and a few plant species. In genomic regions of normal recombination rates, the targets of positive selection have been mapped down to the level of individual genes.

The spectroscopy of the low-lying bands in the special-pair radical-cations of photosynthetic reaction centres - Jeffrey R. Reimers; Michael C. Hutter; Noel S. Hush (Photosynthesis Research, 1998)

The distribution and frequency of microsatellite loci in Drosophila melanogaster - M. D. SCHUG; K. A. WETTERSTRAND; M. S. GAUDETTE; R. H. LIM; C. M. HUTTER; C. F. AQUADRO (Molecular Ecology, 1998)
We report the results of a comprehensive search of Drosophila melanogaster DNA sequences in GenBank for di‐, tri‐, and tetranucleotide repeats of more than four repeat units, and a DNA library screen for dinucleotide repeats. Dinucleotide repeats are more abundant (66%) than tri‐ (30%) or tetranucleotide (4%) repeats. We estimate that 1917 dinucleotide repeats with 10 or more repeat units are present in the euchromatic D. melanogaster genome and, on average, they occur once every 60 kb. Relative to many other animals, dinucleotide repeats in D. melanogaster are short. Tri‐ and tetranucleotide repeats have even fewer repeat units on average than dinucleotide repeats. Our WorldWide Web site (http://www.bio.cornell.edu/genetics/aquadro/aquadro.html) posts the complete list of 1298 microsatellites (≥ five repeat units) identified from the GenBank search. We also summarize assay conditions for 70 D. melanogaster microsatellites characterized in previous studies and an additional 56 newly characterized markers.